Genomic imprinting in the human placenta - Monk, David (American journal of obstetrics and gynecology, 2015)
With the launch of the National Institute of Child Health and Human Development/National Institutes of Health Human Placenta Project, the anticipation is that this often-overlooked organ will be the subject of much intense research. Compared with somatic tissues, the cells of the placenta have a unique epigenetic profile that dictates its transcription patterns, which when disturbed may be associated with adverse pregnancy outcomes. One major class of genes that is dependent on strict epigenetic regulation in the placenta is subject to genomic imprinting, the parent-of-origin-dependent monoallelic gene expression. This review discusses the differences in allelic expression and epigenetic profiles of imprinted genes that are identified between different species, which reflect the continuous evolutionary adaption of this form of epigenetic regulation. These observations divulge that placenta-specific imprinted gene that is reliant on repressive histone signatures in mice are unlikely to be imprinted in humans, whereas intense methylation profiling in humans has uncovered numerous maternally methylated regions that are restricted to the placenta that are not conserved in mice. Imprinting has been proposed to be a mechanism that regulates parental resource allocation and ultimately can influence fetal growth, with the placenta being the key in this process. Furthermore, I discuss the developmental dynamics of both classic and transient placenta-specific imprinting and examine the evidence for an involvement of these genes in intrauterine growth restriction and placenta-associated complications. Finally, I focus on examples of genes that are regulated aberrantly in complicated pregnancies, emphasizing their application as pregnancy-related disease biomarkers to aid the diagnosis of at-risk pregnancies early in gestation.